ARTIFICIAL FEEDING WITH DIFFERENT PROTEIN CONTENT IN SEED CORAL TROUT GROUPER, PLECTROPOMUS LEOPARDUS IN CONTROLLED TANK - Alit, Anak Agung (Aquacultura Indonesiana, 2020)
Coral trout grouper seed have high economic value, but the population in nature has started to decline. The purpose of this study was to obtain a good quality of feed on the growth and stability of seeds of coral trout grouper. Research has been done with experiment container used is fiber tank with size 1m³ counted 6 tanks. The test animals used in the study were the grouper seeds from the culture. The treatments were A = protein content in 48% feed, and treatment B = feed pellet import protein content in feed 55%. Coral trout groupers are kept in fiber tanks. Density of each tank 200 etc /m³ The study used a descriptive design with 2 treatments, each treatment repeated 3 times. Data were analyzed by using ANOVA and at the end of the research was done profit ratio analysis. The results showed that both treatments were significantly different (P <0.05) on survival and daily growth (GR). The highest survival and daily growth in treatment B (SR 97.45%; GR 0,26g/ day) followed by treatment A (SR 85,50 %; GR 0,15g/day). From the economic analysis the best profit B/C ratio was 1.51 treatment B, and followed treatment A was 1.09.